Does social interaction influence the effect of cognitive intervention program? A randomized controlled trial using Go game. (10th December 2018) - Iizuka, Ai; Suzuki, Hiroyuki; Ogawa, Susumu; Kobayashi‐Cuya, Kimi Estela; Kobayashi, Momoko; Inagaki, Hiroki; Sugiyama, Mika; Awata, Shuichi; Takebayashi, Toru; Fujiwara, Yoshinori
Abstract : Objectives: The purpose of this study is to clarify the influence of social interaction on the effect of a cognitive intervention program using Go. Methods: A single‐blind, randomized controlled trial using a classical board game "Go" was conducted. A total of 72 community‐dwelling older adults, without previous experience playing Go, were randomly assigned to three groups: (1) a face‐to‐face group (FG) in which members attended 12 Go group lessons held once a week; (2) a non‐face‐to‐face group (NFG) in which members individually underwent the same Go lessons as the FG using a tablet computer; or (3) a health education control group (CG). The main outcome variable, working memory, was assessed before and after the interventions using the Visual Memory Span Test (VMST) and the Visual Memory Span Backward (VMSB) task. Go performance and additional cognitive domains were also examined. Results: Analysis of covariance revealed that VMST scores significantly improved after the intervention in both the FG and NFG (both P  < .05). Compared with the CG, the effect size of the FG (Cohen's d  = 0.89) was greater than that of the NFG (Cohen's d  = 0.67). Although VMSB scores significantly improved after the intervention in the FG ( P  < .05), no significant changes were observed in other groups. Conclusions: This study showed that Go game could improve visual working memory regardless of social interaction. Furthermore, findings suggested that playing board games face‐to‐face with others is more effective for cognitive function than playing alone.